(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2018)
The administrations should be aware of the necessity of administrative transparency as it is one of the modern management concepts, because it is important to achieve successful administrative development, and to address many administrative problems such as ambiguity of laws and procedures in force, as well as their contribution to the development of administrative organizations and the ability to establish an organizational structure capable of confronting Challenges and variables in the surrounding environment. The objective of the research is to study the reality of the application of administrative transparency through its elements: Integrity, Empowerment, Trust, Accountability and Business Procedures, at the Commercial Bank of Syria in Lattakia. The research was based on the descriptive approach and the survey method. The questionnaire was used as the main source of data and information. The research community was composed of all the employees of the Commercial Bank of Syria in Lattakia. Due to the small size of the research society, the comprehensive enumeration method was adopted. 130 questionnaires were distributed to the workers, 121 were returned to complete statistical analysis and 93.08 %). The results showed that the level of application of administrative transparency in the Syrian Commercial Bank in Lattakia is a high level, with a relative importance (76.68%). تعد الشفافية الإدارية من المفاهيم الإدارية الحديثة التي يتوجب على الإدارات الواعية ضرورة الآخذ بها, لما لها من أهمية في إحداث التطوير الإداري الناجح, ومعالجة العديد من المشاكل الإدارية مثل غموض القوانين والإجراءات المعمول بها, فضلاً عن مساهمتها في تطوير التنظيمات الإدارية والقدرة على إنشاء بناء تنظيمي قادر على مواجهة التحديات والمتغيرات في البيئة المحيطة. هدف البحث إلى دراسة واقع تطبيق الشفافية الإدارية من خلال عناصرها: النزاهة, والتمكين والثقة, والمساءلة, وإجراءات العمل, وذلك في المصرف التجاري السوري باللاذقية. اعتمد البحث على المنهج الوصفي, وأسلوب المسح, حيث اُستخدمت الاستبانة كمصدر رئيس في الحصول على البيانات والمعلومات. تكون مجتمع البحث من جميع العاملين في المصرف التجاري السوري بمدينة اللاذقية, ونظراً لصغر حجم مجتمع البحث تمّ اعتماد طريقة الحصر الشامل, حيث تمّ توزيع (130) استبانة على العاملين, وأعيد منها (121) استبانة كاملة وصالحة للتحليل الإحصائي, وبنسبة استجابة بلغت (93.08%). أظهرت النتائج أنّ مستوى تطبيق الشفافية الإدارية في المصرف التجارية السوري بمدينة اللاذقية هو مستوى مرتفع, وبأهمية نسبية (76.68%).